THE DYNAMICS OF RATIFICATION ACTS OF INTERNATIONAL TREATY UNDER INDONESIAN LEGAL SYSTEM - Dinata, Ari Wirya (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2021)
The Ratification Act is a legal product that states Indonesia's commitment to an international treaty. The constitutionality of these laws has been tested before the Constitutional Court. In its decision, the Constitutional Court stated that the Ratification Acts is the object of judicial review as stipulated in article 24 C paragraph (1) of the 1945 Constitution. Even though there were two differences of opinion in the verdict on the ASEAN Charter Ratification Laws review, namely the Justice: Hamdan Zoelva and Maria Farida. The two judges categorized the Laws on the Ratification of International Treaties, not in the category of laws reviewed by the Constitutional Court. This decision explains the position of the Ratification Law in the Indonesian legal system and its future implications. This paper discusses the position of the Ratification Acts under the Indonesian legal system and the implications that will occur after the future Constitutional Court decisions on the development and relations of national law and international law. This writing uses secondary data and also primary, secondary, and tertiary legal material. This writing found the inconsistency of Indonesia in making ratification acts of International Law. It emerges that implication to the status of ratification acts. Moreover, The Constitutional Court decision tries to clarify ratification acts under the Indonesian legal system.